2008
DOI: 10.1007/bf03195627
|View full text |Cite
|
Sign up to set email alerts
|

Turner syndrome mosaicism: an unusual case with a de novo large dicentric marker chromosome: mos 45,X/46,X, ter rea(X;X)(p22.3;p22.3)

Abstract: X/X translocations are quite rare in humans. The effect of this anomaly on the phenotype is variable and depends on the amount of deleted material and whether the chromosomes are joined by their long or short arms. We report an unusual case of Turner syndrome mosaicism in a 16-year-old girl, who was referred to our Institute for primary amenorrhoea associated with short stature. Endocrine evaluation revealed hypergonadotropic hypogonadism, which required a study of the karyotype. Cytogenetic analysis, performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…In the present study's patients, 45,X was the most prevalent aberration observed (46.4%), followed by diverse mosaicism (38%), while pure structural anomalies accounted for only 13.4% of cases. Similarly, previous studies from Serbia, Italy, Indonesia and Kuwait revealed 45,X as a more prevalent karyotype with frequencies of 48.4% (Djordjević et al, 2010), 50% (Nucaro et al, 2008), 41.1% (Marzuki et al, 2011) and 63% (Abulhasan et al, 1999), respectively. Approximately 95-99% of 45,X embryos fail to survive to term, although they demonstrate mild phenotypic abnormalities compared with autosomal aneuploidy (Hook and Warburton, 1983).…”
Section: Discussionsupporting
confidence: 78%
“…In the present study's patients, 45,X was the most prevalent aberration observed (46.4%), followed by diverse mosaicism (38%), while pure structural anomalies accounted for only 13.4% of cases. Similarly, previous studies from Serbia, Italy, Indonesia and Kuwait revealed 45,X as a more prevalent karyotype with frequencies of 48.4% (Djordjević et al, 2010), 50% (Nucaro et al, 2008), 41.1% (Marzuki et al, 2011) and 63% (Abulhasan et al, 1999), respectively. Approximately 95-99% of 45,X embryos fail to survive to term, although they demonstrate mild phenotypic abnormalities compared with autosomal aneuploidy (Hook and Warburton, 1983).…”
Section: Discussionsupporting
confidence: 78%